2022
DOI: 10.4103/sja.sja_198_22
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of THRIVE oxygenation and intra-operative lung-protective ventilation in morbidly obese patients undergoing neurosurgical procedures

Abstract: The conduct of anesthesia in morbidly obese patients undergoing neurosurgical procedures can be challenging considering the multi-system organ involvement. Implementation of conventional lung-protective ventilation in morbidly obese patients can have a negative impact on the intra-cranial dynamics. We report a series of three patients with morbid obesity and a difficult airway for the neurosurgical procedure. The patients were oxygenated with high-flow oxygen devices to ensure an adequate oxygen reserve in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…During apneic oxygenation, alveolar oxygen uptake occurs due to concentration gradient allowing maintenance of oxygenation and high flows and cardiogenic oscillations improve the clearance of CO 2. [ 2 3 6 ] THRIVE combines the advantage of standard apneic oxygenation with CPAP and gaseous exchange through flow-dependent dead space flushing. [ 3 ] Patel et al [ 3 ] showed safe apnea time of 5–65 mins without arterial desaturation and the rate of increase in ETCO 2 was 0.15 kPa.…”
Section: Discussionmentioning
confidence: 99%
“…During apneic oxygenation, alveolar oxygen uptake occurs due to concentration gradient allowing maintenance of oxygenation and high flows and cardiogenic oscillations improve the clearance of CO 2. [ 2 3 6 ] THRIVE combines the advantage of standard apneic oxygenation with CPAP and gaseous exchange through flow-dependent dead space flushing. [ 3 ] Patel et al [ 3 ] showed safe apnea time of 5–65 mins without arterial desaturation and the rate of increase in ETCO 2 was 0.15 kPa.…”
Section: Discussionmentioning
confidence: 99%